Effectiveness of pirfenidone for idiopathic pulmonary fibrosis associated with pleuroparenchymal fibroelastosis‐like lesions and nonspecific interstitial pneumonia. (26th October 2020) - Sakamoto, Susumu; Shimizu, Hiroshige; Isshiki, Takuma; Nakamura, Yasuhiko; Kurosaki, Atsuko; Isobe, Kazutoshi; Homma, Sakae
Abstract: Background: Pirfenidone treatment can slow decline in forced vital capacity (FVC) in idiopathic pulmonary fibrosis (IPF). However, its effects for usual interstitial pneumonia (UIP) with pleuroparenchymal fibroelastosis‐like lesions (UIP+PPFELL) and UIP with nonspecific interstitial pneumonia (UIP+NSIP) are unclear. Objectives: The aim of study is to assess pirfenidone effectiveness for UIP+PPFELL and UIP+NSIP. Methods: We retrospectively analysed data from 58 IPF patients treated with pirfenidone more than 6 months. The outcomes of interest were 6‐month follow‐up pulmonary function test results, progression‐free survival (PFS) and overall survival (OS). Treatment was considered effective if FVC decline was <5% during the 6‐month period. We compared clinical characteristics, effectiveness, PFS and OS between patients with typical IPF (n = 32), UIP+PPFELL (n = 12) and UIP+NSIP (n = 14). Results: Data from 58 IPF patients were analysed. At the 6‐month follow‐up examination, treatment was deemed effective for 9 of 14 (64%) UIP+NSIP patients, 6 of 12 (50%) UIP+PPFELL patients and 14 of 32 (44%) patients with typical IPF. The 6‐month decline in FVC before treatment was greater than that after starting treatment in the UIP+NSIP (−210 vs. −57 mL; P  = 0.09), UIP+PPFELL (−370 vs. −89 mL; P  = 0.001) and typical IPF (−172 vs. −85 mL; P  = 0.37). PFS did not significantly differ between the three groups. OS was significantly shorter for UIP+PPFELL (312 days) than for UIP+NSIP (545 days) and typical IPF (661 days). Conclusions: Pirfenidone decreased the decline in FVC in patients with UIP+PPFELL and UIP+NSIP, as well as in those with typical IPF. However, outcomes were worse for patients with UIP+PPFELL.